Evaluasi Proses Bisnis Produksi Garmen Menggunakan Metode Quality Evaluation Framework (QEF) (Studi Kasus: PT. Eratex Djaja, Tbk Probolinggo) - Mumtazah Rizti Arini; Nanang Yudi Setiawan; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PT. Eratex Djaja, Tbk Probolinggo is a company of garment production focusing on export sales. The company's main product is pants. Because the company is working on garment production, the most important thing is the production process. The production process has the greatest impact on the final result of the product. As a large company, PT. Eratex Djaja, Tbk Probolinggo applies Standard Operational Procedure (SOP) as guidelines for the business process. However, on daily basis, not all processes are performed in accordance with the procedure. The company has some defective or rejected products. Based on the indication of problems that have already found out, this research is evaluating the business process in the production activity using Quality Evaluation Framework (QEF) to find out non-functional problems in the business process. The first to determine non-functional requirements and reformed main processes using Business Process Model and Notation (BPMN). The next to determine the quality factor, company target and calculating, according to the questions in the QEF method. The results of calculations that are not in accordance with the target are 5 of 16 quality factors. They are not in accordance with company targets is analyzed using the Fault Tree Analysis (FTA) method to find out the root cause of the problem. The result of the FTA is expected to help minimize the problems in the current business process.